Field application of farmfood safety risk assessment (FRAMp) tool for small and medium fresh produce farms - Soon, J.M.; Davies, W.P.; Chadd, S.A.; Baines, R.N, (Elsevier, 2013)
The objective of this study was to develop a farm food safety-risk assessment tool (FRAMp) which serves as a self-assessment and educational tool for fresh produce farms. FRAMp was developed in Microsoft® Excel spreadsheet software using standard mathematical and logical functions and utilised a qualitative risk assessment approach for farmers to evaluate their food safety practices. The FRAMp tool has since been tested on 12 fresh produce farms throughout UK. All the farms determined that FRAMp was interesting but 17% found it too long while 25% of the farms felt the tool was too complicated. The instructions on FRAMp usage were revised and farmers were given the options to skip and select specific steps in the farm risk assessment. The end users (farmers/farm managers) determined that developing their own action plans and using it as proof of assessment for future third-party audits were most useful to them. FRAMp tool can be described as an illustrative risk ranking tool to facilitate farms to identify potential risk factors during their crop production